Design and CFD simulation of guide vane for multistage Savonius wind turbine - Devin, Dionisius; Halim, Levin; Arthaya, Bagus Made; Chandra, Jonathan (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2023)
This study proposes improving the performance of a fixed-axis multistage Savonius wind turbine by integrating a sixbladed guide vane. Guide vanes aim to direct the incoming wind towards the blades of the Savonius wind turbine so that it can increase the performance value of the turbine itself. There are two methods, the first method is computational fluid dynamics (CFD) simulation to evaluate the best performance guide vane angle variations. The second method is implementing real conditions using 3 m/s until 4.2 m/s wind speed. The implementation of the guide vane to the wind turbine will consider four (4) variants of angles (0°, 20°, 40°, and 60°). The purpose of testing with four kinds of guide vane angles is to find out which guide vane angle can provide the best results among other guide vane angles. This research proposed the initial design of the guide vane addition to the multistage Savonius wind turbine with a fixed rotary axis. From the CFD simulation, the implementation of a guide vane can improve the performance of the multistage Savonius wind turbine with a fixed rotary axis. On the other hand, for the proposed initial design in this research, the 20° angle of guide vane gives the best result compared to the 0°, 40°, 60°, and without guide vane.